Pselaphinae of the Cameroon Volcanic Line. Part 1. New Pselaphinae (Coleoptera, Staphylinidae) from the island São Tomé - Hlaváč, Peter; Baňař, Petr (Zootaxa, 2022)
A new genus of Pselaphinae, Reichentomica gen. nov., and three new species, Reichentomica tasani sp. nov., Afroplectus turneri sp. nov., and Parasimus saotomicus sp. nov., are described for the first time from the island São Tomé. All three species were collected at the same locality close to Jardim Botânico do Bom Successo (00°16′31′′N, 06°36′14′′E) using flight intercept trap in the tropical forest at the elevation of 1324 m.